Application of SWOT Analysis in Efforts to Develop Strategies for the Credit Union Bahtera Sejahtera Savings and Loan Cooperative - Agustinus Saperius Kwure; Konstantinus Pati Sanga; Fransiscus De Romario; Magdalena Nona Ice (International Publisher (YAPENBI), 2025)
This study aims to analyze the strengths, weaknesses, opportunities, and threats in the development of strategies for KSP CU Bahtera Sejahtera through the application of SWOT analysis. The Research was conducted using a descriptive qualitative approach involving interviews with managers, financial staff, and cooperative members. The results of the study indicate that the cooperative has internal strengths, including friendly service, competitive loan interest rates, and strong solidarity among members. However, the weaknesses found include a lack of member understanding of cooperative principles and limitations in the application of digital technology. External opportunities that cooperatives can take advantage of include increasing public awareness of financial literacy and support from the government. Meanwhile, external threats come from fintech competition and changes in financial regulations. Based on these findings, this study recommends that cooperatives improve member literacy, develop digital infrastructure, and strengthen cooperative identity to remain competitive and grow sustainably. The application of SWOT analysis combined with the Resource-Based View theory provides a strong strategic foundation for the future development of cooperatives.